Perfil atual e ideal dos gerentes de enfermagem de um hospital universitário do Estado do Ceará à luz da gestão por competências - Albuquerque, Elivane de Oliveira Pereira (2015)
The management of nursing services is a complex activity and requires professional competence. Changes in health care demand of professional nurses managers a more flexible and adaptive profile, being necessary to mobilize new skills. This study guides on the skills required to manage nursing considering the technological and administrative changes observed in public hospitals. Presents the new management scenarios and some aspects required for acquiring skills such as knowledge, attitudes and opportunities. It’s considered that the nurse manager has the responsibility to provide a learning environment where workers can acquire new skills and exercise them freely. The research question of this study was: what core competencies the nursing manager must have to manage a health institution and what would be the ideal profile for this manager? The overall objective, therefore, was to identify the current profile of the nursing manager, comparatively analyzing this real profile with the ideal inherent profile in the current literature. The research exploratory and descriptive nature we used a combination of qualitative methods to quantitative (qualitative and quantitative) and is based on the concept of management by competence and their attributes: knowledge, skills and attitudes. It consisted of a Survey involving 36 nurses managers of units of a federal public hospital, in Fortaleza, the University Hospital Walter Cantídio (HUWC). Data were collected from November 2014 to January 2015, through electronic questionnaire on google docs. The population was predominantly female (100%) and aged between 48 and 53 years (36,1%). The results revealed the perception of respondents on the current profile of professional competence ideal for the exercise of managerial activities of HUWC, highlighting the attributes related to knowledge management and strategic and operational planning skills with leadership skills and teamwork, attitude and leadership and professional ethics. It was found that 41% of managers have between 6 and 10 years of service in management position. The profile for managing, predominant characteristics: leadership (33%), teamwork (30%) and communication / good interpersonal skills (28%). From the results, it is clear that managers know what it takes to manage a highly complex hospital, confirmed the level of agreement with these attributes racing knowledge, skills and attitudes. The profile indicates found in similar conception of the collaborators, a professional with ethical, technical and scientific knowledge, ability to manage and lead your team, and committed to the institution. While responses were overestimated, its effects were minimized and not hindered the search results because the correlation between the variables. Thus, it appears that there is commitment of the nursing managers to develop their management skills. However, this provision has not been sufficient element to overcome the difficulties of political and economic order that underlie a Public Hospital Complex.